Cruising Under and Post the COVID Pandemic: Toward Realization of the United Nations’ Sustainable Development Goals - Majid Eskafi; Poonam Taneja; Gudmundur F. Ulfarsson (Journal of Marine Science and Engineering, 2022)
Maritime sectors have always dealt with uncertainties and disruptions. The COVID pandemic confronted the cruise industry with profound, wide-ranging, and lasting challenges while disrupting normal operations. Although the cruise industry contributes to the implementation of the United Nations Sustainable Development Goals (UN SDGs), resumption and sustainable cruising requires the industry to adapt to the challenges presented. To this end, the paper suggests adaptive actions for the cruise sector to respond to the pandemic and links the actions to the UN SDGs to highlight their sustainable contributions. A system thinking approach is applied and a literature review is conducted to identify suitable adaptive actions. This paper shows the importance of UN SDGs 3, 4 and, in particular, 17 for sustainable cruising. The results of this paper provide support for informed decision-making to increase the cruise industry’s sustainability. This paper recommends that stakeholders: 1- identify drivers and barriers of sustainable cruising, 2- adapt to changes and embrace the UN SDGs, as they provide a platform for realizing sustainability, and 3- use educational programs to improve and transfer knowledge on sustainable cruising between academia and policymakers.